Impact of Work Discipline, Work Environment, Communications and Motivation on Employee Performance in PT. KAI Gubeng Surabaya - Siti Rosyafah; Elly Yuniar Nitawati; Nurul Iman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this study is to see how the work discipline, work environment, communication, and motivation of employees affect their performance. This study involved a staff member of Gubeng Surabaya's PT. KAI, consisting of 217 people. Purposive sampling process using certain standards. This research is a quantitative type. Double linear regression analysis applied to the research model. This study showed that the variables of work discipline, work environment, communication, and motivation have a significant influence on employee performance, both individually and collectively. The work environment, motivation, communication, and discipline were the four free variables that simultaneously had a substantial impact on the employee's performance, as demonstrated by the results, which had a significance value on the F test of 0,000, or less than 0.05. Results of the analysis of the determination coefficient (R2) indicated that the value of R2 was 64.8% of the influence of the variable free on the dependent variable. Other variables not included in this study affect the remaining portion.